2012
DOI: 10.1161/circulationaha.112.114140
|View full text |Cite
|
Sign up to set email alerts
|

From Concept to Reality

Abstract: Perseverance is not a long race: it is many short races one after another.-Walter Elliott, 19th Century spiritual writer T he treatment and outcome of patients with ST-segment elevation myocardial infarction (STEMI) has improved dramatically over the 30 years since I graduated from medical school. In 1982, bed rest, treatment of complications such as ventricular arrhythmias or mural thrombus and prayer (for those so inclined) were the standard of care. In the first decade, pharmacological therapy was developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…20 Such integrated systems of care based on direct EMS transport of STEMI patients to high-volume PCI centers has shown promise 23,35 and have demonstrated success even when serving extensive rural areas, achieving FD2B times significantly below the national average. 18,[35][36][37] Multiple efforts to regionalize revascularization services have demonstrated that further improvements are possible at a state-wide level, resulting in a decrease in FD2B time to 103 minutes, with 39% of patients achieving FD2B ≤90 minutes.…”
Section: Systems Of Carementioning
confidence: 99%
“…20 Such integrated systems of care based on direct EMS transport of STEMI patients to high-volume PCI centers has shown promise 23,35 and have demonstrated success even when serving extensive rural areas, achieving FD2B times significantly below the national average. 18,[35][36][37] Multiple efforts to regionalize revascularization services have demonstrated that further improvements are possible at a state-wide level, resulting in a decrease in FD2B time to 103 minutes, with 39% of patients achieving FD2B ≤90 minutes.…”
Section: Systems Of Carementioning
confidence: 99%
“…(2007) stressed that the study was not designed to examine mortality and that inferences based on their outcomes should be made with great caution. Henry (2012) described the RACE program as a model case of voluntary participation of all hospitals statewide. Glickman et al.…”
Section: Resultsmentioning
confidence: 99%
“…Continued efforts to coordinate care and facilitate real-time decision-making between STEMI referral hospitals, emergency medical services, and STEMI receiving hospitals should help mitigate these logistic barriers. 26 Fortunately, since 2008, the proportion of patients transferred directly to the cath lab has increased significantly ( Figure 2). Finally, a previous study found a statewide prehospital STEMI strategy to bypass closer hospitals without PCI capability resulted in substantially shortened reperfusion delays, 25 yet this strategy is not possible for all patients and geographic areas.…”
Section: Discussionmentioning
confidence: 99%